PREOPERATIVE CBCT ASSESSMENT OF DONOR SITE- SYMPHYSIS AND RAMUS BUCCAL SHELF FOR ALVEOLAR RIDGE AUGMENTATION - Hristo Stoyanov; Elitsa Deliverska (Peytchinski Publishing, 2018)
Introduction: Mandibular block autografts have been used extensively for alveolar ridge augmentation with great success and include the symphysis and ramus buccal shelf as donor sites. Objectives: Purpose of our study is to analyze preoperative CBCT assessment of donor sites- (symphysis and ramus buccal shelf) for ranges of autogenous block graft. Material and Methods: In our study, we have analyzed with CBCT these donor sites in 15 patients and were determined the osteotomy lines of the graft depends on the limiting anatomical critical structures. Also according to CBCT with 3D printing could be done stereolithographic models and 3D cutting models for optimizing surgery. Results: Symphysis can provide a range of dense cortical cancellous bone ranging from 17,7/7,65/6,68 mm, in contrast to a typical ramus buccal shelf block graft that is 9/9,2/8,1 mm. In symphisis area, there were observed a significant difference in width of the block at the level of the second incisor and canine. Also, the thickness of the graft differs in cranial and in caudal position. About bone graft from the buccal shell of mandibular ramus, thickness decreases from cranial to caudal direction as the measurement is at about 8mm. The width of the block is bigger in a cranial direction and smaller at the half level of its height. Conclusion: Preoperative assessment of donor site is essential for the success of the procedure. These grafts can be used for predictable horizontal augmentation of 5 to 7 mm and vertical augmentation of up to and including 6 mm.